Perumpamaan Bahasa Alas pada Masyarakat Aceh Tenggara - Al Furqan Al Furqan; Dhea Anggia Desky (Master Bahasa, 2022)
This research is entitled "Parables in the Alas Language of the People of Southeast Aceh". The problem in this research is what are the forms and meanings of parables in the Alas language in the people of Southeast Aceh. The purpose of this study is to describe the types and meanings of parables in the Alas language in the people of Southeast Aceh. This study uses a qualitative method with a descriptive method. The data in this study amounted to fifty data with details of seventeen metaphorical parables and thirty-three personification parables. The data sources of this research were obtained from native speakers of the Alas language. Data collection was carried out by steps (1) transcribing the data, (2) translating the data, (3) compiling the data, (4) analyzing the data, and (4) concluding the data. The results of this study indicate that the parables in the Alas language in the people of Southeast Aceh have metaphorical parables and personification parables. The parable describes the human character. The use of this parable is to soften the intent of the conveyer of the expression so that those who hear or receive the expression do not feel flattered if the parable is in the form of praise.